The church and the land: the National Catholic Rural Life Conference and American society, 1923-2007 - Bovée, David S. (Catholic University of America Press, 2010)
Preface -- Catholic rural America to 1920 -- O'Hara and the formation of the conference -- The Catholic rural population problem -- The Great Depression -- Programs to meet the crisis -- Inside the NCRLC -- Ligutti takes the helm -- The conference becomes international -- Helping developing countries -- The end of the Ligutti era -- Organizing for social involvement -- For the family farm in the age of agri-business -- Fighting poverty -- Stewardship of the planet -- Catholic and American : the NCRLC over eight decades